Solutions to improve structure and operation of strategy and policy research organizations serving state management under ministries and ministerial-level - Minh Hanh, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
In the national system of science and technology (S&T) organizations, institutions in charge of policy and strategy studies under ministry and ministerial-level agency (hereinafter referred to as Ministry institutions) are those entities being assigned with research function with a view to providing scientific and practical basis for development of strategies, mechanisms and policies for state management of the host ministry. By conducting study and analysis of international experiences and practices of Vietnam, the author of this paper proposed some solutions that should be simultaneously undertaken for further improvement of the performance of this kind of organization, in respect of (1) Creating a freedom, democracy environment for social science research; (2) Improved mechanism of assigning research task to ministry institutions in charge of policy and strategy study for state management; (3) Cost-effective mechanism of steering, coordination and cooperation in policy research and development for management and (4) Autonomy of ministry institutions in charge of policy and strategy research in respect of organization and human arrangement with the aim to improve the organizational and operational model of this kind of institution in the future. Code: 14122401